Bilateral nephromegaly due to direct leukemic cell invasion in the initial and relapse phases of T-cell acute lymphoblastic leukaemia: A case report. Issue 51 (23rd December 2021) - Tamura, Yoshifuru; Sumiyoshi, Ritsu; Yamamoto, Tadashi; Hayama, Yuto; Fujigaki, Yoshihide; Shibata, Shigeru; Sasajima, Yuko; Tashiro, Haruko
Abstract: Rationale: T-cell acute lymphoblastic leukemia is a relatively uncommon disorder in adults. Kidneys are not frequently invaded by leukemic cells, and patients with adult ALL showing nephromegaly as an initial presentation are rare. Patient concerns: A 54-year-old man was referred to our institution for mild anemia and thrombocytopenia. Laboratory tests showed bicytopenia with abnormal lymphoid cells in the peripheral blood and mild renal dysfunction. Diagnosis: Ultrasonography and computed tomography (CT) revealed bilateral enlargement of the kidneys. [18F]-fluorodeoxyglucose positron emission tomography/CT demonstrated a strong increase in metabolic uptake in the bilateral kidneys. A kidney biopsy revealed a leukemia invasion into the parenchyma. Based on the lymphocytic repertoire, the patient's condition was diagnosed as T-cell acute lymphoblastic leukaemia. Interventions: The patient received hyper-cyclophosphamide, vincristine, adriamycin, and dexamethasone and high-dose methotrexate and cytarabine as induction chemotherapy. After his leukemia relapsed, he received nelarabine as a second induction therapy and underwent haploidentical peripheral blood stem cell transplantation. Outcomes: Complete remission (CR) was achieved after chemotherapy. Chemotherapy also improved renal function associated with the normalization of bilateral nephromegaly. Repeated [18F]-fluorodeoxyglucose - positron emission tomography/CT posttreatment showedregression of metabolic uptake in the bilateral kidneys. The patient underwent cord blood transplantation at the first CR, but his leukemia relapsed 9 months later. At relapse, bilateral nephromegaly reappeared. Then, the second induction therapy induced CR for at least 10 months after induction therapy. Lessons: Although rare, ALL in the initial and relapsed phases can be associated with bilateral nephromegaly and renal impairment due to the invasion of leukemic cells into the parenchyma with or without abnormal leukemic cells in circulation. Leukemia is an important differential diagnosis of renal impairment with bilateral nephromegaly.